Remote limb ischemic post-conditioning attenuates ischemia-reperfusion injury in rat skin flapby limiting oxidative stress - Zhang,Yi (2016)
PURPOSE: To investigate the effect of remote ischemic post-conditioning (RIPoC) against ischemia-reperfusion (I/R) injury on flaps of rats. METHODS: Sprague-Dawley rats were randomized into the Sham, Control, RIPoC1 and RIPoC2 groups. All the animals were submitted to a 5×4 cm superficial inferior epigastric artery flap. Eight hours of flap ischemia was induced and two protocols of limb RIPoC were applied. Tissue MDA level and SOD activity in 24-h reperfusion were assessed. Flap survival was assessed 7 days postoperatively. RESULTS: Compared to the Control group, the RIPoC1 group showed statistically decreased MDA level at 6-, 12-, and 24-h reperfusion (P = 0.01, P < 0.01 and P < 0.01, respectively), and statistically increased SOD activity at 12- and 24-h reperfusion (P < 0.05 and P < 0.01, respectively). Flap survival rate on the 7th day was significantly higher in the RIPoC1 group than the control group (47.9 ± 6.4 vs . 29.4 ± 7.1 %, P < 0.01). CONCLUSION: Three cycles of 5-min Limb remote ischemic post-conditioning rather than a single cycle of 15-min limb RIPoC has protective effect on flaps against ischemia-reperfusion injury by attenuating oxidative stress.